Analisa Pengembangan Pada Penerimaan Peserta Didik Baru (PPDB) MIS SIROJUL ANWAR - Aryanto Nur; Farhan Syahrial; Carisa Alverina Andika Gamar; Nur Vina Silviani; Azzahra Nur Hidayah (Journal Of Informatics And Busisnes, 2024)
MIS Sirojul Anwar is an educational institution located in Kampung Bojong Sempu RT. 04 RW.06 West Cilebut Village, Sukaraja District, Bogor Regency who has the desire to provide educational services to the community as best as possible. Currently, not many schools use an online registration system, some schools still use an offline registration system which is carried out using a paper registration form which is input into digital form using a computer and data processing software, so that with this method there is concern that the paper form will get scattered so that it doesn't happen. recorded and during the data input process there will be data duplication. MIS Sirojul Anwar carries out the New Student Admissions (PPDB) process at school, students come and fill out the form provided by the committee, usually carried out during class promotion holidays, then the stage of collecting required documents, then continues with interviews with prospective students and their parents or guardians. After the registration and selection process, students wait for the announcement. With the description of the process above, filling out the form is carried out repeatedly, data filled in offline cannot be monitored by prospective students, even if an error occurs in inputting data, prospective students cannot change it and it will be a student data error. Selection results also cannot be displayed online. so that prospective students only wait for the results when the registration process ends.